Mono-Chronological ‘Post’: Synchronization of the Meanwhiles of Nations in Antun Barac’s and Pavle Popović’s Histories of Yugoslav Literature and the (Post)-Yugoslav Literature - Mijatović, Aleksandar (Poznańskie Studia Slawistyczne, 2019)
In this paper, I approach to the relationship between the art and the democracy via discussion of two histories of Yugoslav literatures. I propose and try to defend a thesis that both accounts of the history of Yugoslav literatures synchronize temporalities of the different national literatures, reducing thereby differences between them. Both histories substantialize Yugoslav literature as a remnant of the lost community. They argue that immediacy of that community had dissolved into the variety of nations, which led separate lives under the rule of empires. In the name of that mythical past, heterogeneous temporalities are synchronized to the single temporal flow. However, the similar substantializing operation and synchronization is present in the more recent concept of (post)-Yugoslav literature.